"We Have to Meet Those Clients Where They're at" ‐ Michigan Behavioral Health Providers' Responses to Telehealth Policy Changes during COVID‐19. (15th September 2021) - Schoebel, Victoria; Page, Cory; Beck, Angela; Buche, Jessica; Gaiser, Maria; Wayment, Caitlyn; Mauri, Amanda
Abstract : Research Objective: To understand the impact of state and federal policy changes during the COVID‐19 pandemic on use and effectiveness of telebehavioral health based on provider experience, Study Design: Between July and August 2020, researchers conducted one‐hour interviews with 31 Michigan‐based behavioral health providers from 15 counties. These semi‐structured interviews included the following topics: (1) Experience with telebehavioral health prior to, and during, the pandemic, (2) Changes in cost of, access to, and quality of care between in‐person and telebehavioral health services, and (3) Telebehavioral health's impact on providers and clients. The interviews were recorded, transcribed, and later analyzed with Dedoose™ software to identify common themes between responses. Population Studied: Interviewees included a psychiatrist, psychologists, registered nurses, clinical social workers, mental health counselors, substance use disorder counselors, applied behavior analysts, and peer support specialists. Principal Findings: Telebehavioral health provision increased during the pandemic, with all interviewees reporting providing telebehavioral health services ‐ 19 for the first time. All interviewees agreed that newly‐enacted state and federal policies made it legally and financially viable to continue safely providing services during the pandemic. Fourteen interviewees reported increased job satisfaction and decreased feelings of burnout. No interviewees reported a breach of health data as a result of using non‐public facing audio‐visual communications. Overall, interviewees agreed telebehavioral health services were at least as effective as in‐person services. Clients with certain conditions (social anxiety, post‐traumatic stress disorder) seemed to respond better to telebehavioral health services. Clients with other conditions (substance use disorder, developmental disabilities) responded less favorably. Thirty interviewees reported clients were satisfied with telebehavioral health services, with some clients preferring them over in‐person services. Twenty‐eight reported telebehavioral health reduced or removed barriers that would have otherwise prevented these clients from receiving care, such as the need to arrange for transportation, childcare, or time off from work. This resulted in decreased no‐show rates and more regular contact between providers and clients. Access to care for geographically isolated populations increased when audio‐only telebehavioral health was authorized; these populations used to have to travel further for care, and often lacked high‐speed internet and internet‐connected devices necessary for audio‐visual telehealth services. Conclusions: Despite telebehavioral health's effectiveness and widespread client approval, interviewees expressed that their current work with telehealth was only possible because of recent policy changes. Should those policies revert back, providers may not be able to continue to provide these services. For some clients, such as those who are geographically isolated and unable to engage with anything but audio‐only telehealth, reverting these policies would mean notable barriers and/or losing access to care entirely. Implications for Policy or Practice: In Michigan, policy implications for both private and public insurances include continuing audio‐only telehealth authorization and improving coverage of telebehavioral health by instituting service and reimbursement parity policies. Such policies could be enacted through Medicaid plan amendments or amendments to Michigan's Insurance Code. For federal policymakers, implications include amending HIPAA to improve acceptability of non‐public facing audio‐visual communications and extending certain provisions of the CARES Act, such as allowing audio‐only telehealth as a modality of last resort, through new laws and regulations. Primary Funding Source: Institute for Healthcare Policy and Innovation.